Enhancing spatial ability through sport practice: Evidence for an effect of motor training on mental rotation performance - Moreau, D.; Clerc, J.; Mansy-Dannay, A.; Guerrien, A. (Journal of Individual Differences, 2012)
This experiment investigated the relationship between mental rotation and sport training. Undergraduate university students (n = 62) completed the Mental Rotation Test (Vandenberg & Kuse, 1978), before and after a 10-month training in two different sports, which either involved extensive mental rotation ability (wrestling group) or did not (running group). Both groups showed comparable results in the pretest, but the wrestling group outperformed the running group in the posttest. As expected from previous studies, males outperformed women in the pretest and the posttest. Besides, self-reported data gathered after both sessions indicated an increase in adaptive strategies following training in wrestling, but not subsequent to training in running. These findings demonstrate the significant effect of training in particular sports on mental rotation performance, thus showing consistency with the notion of cognitive plasticity induced from motor training involving manipulation of spatial representations. They are discussed within an embodied cognition framework.